Fluorescence Detecting of Paraquat and Diquat Using Host–Guest Chemistry with a Fluorophore-Pendant Calix[6]arene - Ermanno Vasca; Francesco Siano; Tonino Caruso (Sensors, 2023)
Paraquat (PQ) and diquat (DQ), some of the most widely used herbicides in the world, both present a high mortality index after intentional exposure. In this paper, a fluorescence sensing method for PQ and DQ, based on host–guest molecular recognition, is proposed. Calix[6]arene derivatives containing anthracene or naphthalene as pendant fluorophore at their lower rim recognize DQ and PQ in hydroalcoholic solution with a broad linear response range at the μg L−1 level concentration. The linear response ranges were found from 1.0 to 18 μg L−1 with the detection limit of 31 ng L−1 for paraquat, and from 1.0 to 44 μg L−1 with the detection limit of 0.16 μg L−1 for diquat. The recognition process is detected by following the decrease in the fluorescence emission consequent to complexation. The proposed quenching method has been applied to the determination of paraquat in drinking water samples.